The influence of human capital on market orientation and micro, small, and medium enterprises (MSMEs) performance - Pane, Ayu Sartika; J. Kamuri, Klaasvakumok; Manongga, Irience R.A.; Anabuni, Andrias U.T. (Jurnal Mantik, 2025)
MSMEs must adapt to globalization and competition, with human resources being crucial for profitability. In Kupang City, MSME actors struggle with competitive strategies, innovation, and collaboration due to low education and skills. This study investigates the impact of human capital on market orientation and performance among 99 MSME actors, using stratified random sampling and Partial Least Squares (PLS) analysis. Results indicate that human capital significantly influences market orientation (49.5% correlation) and MSME performance (path coefficient of 0.228, t-statistic of 2.518, p-value = 0.012). Market orientation also positively affects performance (path coefficient of 0.438, t-statistic of 4.465, p-value = 0.000). The model shows good predictability (R-squared of 0.245 for market orientation and 0.343 for performance). The study concludes that enhancing human capital and adopting effective market orientation strategies are vital for MSME performance improvement, providing empirical support for the literature on these factors in developing countries like Kupang City